THE FULL BINARY TREE CANNOT BE INTERPRETED IN A CHAIN. - RABINOVICH, ALEXANDER (Journal of Symbolic Logic, 2010)
We show that for no chain C there is a monadic-second order interpretation of the full binary tree in C.